Characteristics of Dengue Hemorrhagic Fever Vectors in North Kembangan Sub-district, Kembangan District, West Jakarta City - Dessy Paiman; Onny Setiani; Budiyono Budiyono (Majalah Kesehatan Indonesia, 2023)
Dengue fever is a health problem in Kembangan Utara urban village, Kembangan sub-district. There were 136 cases of DHF in September 2022 with a population of 68,841 with an IR of 197.6. Considering the high number of cases, it is necessary to coordinate vector density survey and Dengue virus examination in Aedes aegypti mosquitoes. Objective: To coordinate activities for vector density surveys and Dengue virus testing in Aedes aegypti mosquitoes. Observational research methods were carried out by observing the presence of Aedes aegypti larvae in terms of breeding sites. Observations were made using observation sheets. Statistical analysis to describe the description of breeding sites, density, and types of breeding sites that are dominantly preferred by Aedes aegypti mosquito larvae. The results of the mosquito larva survey in 100 houses showed that 31 houses were positive for larvae (ABJ: 70%), meaning that the area of North Kembangan Village, Kembangan Subdistrict, West Jakarta is at high risk for dengue transmission. Mosquito catching in 100 houses showed that 80 houses found 142 mosquitoes consisting of 123 Culex genus, 8 female Aedes aegypti mosquitoes and 11 male Aedes aegypti mosquitoes. Dengue virus examination of female Aedes aegypti mosquitoes from the rearing process showed positive results for Dengue virus. Conclusion Dengue virus examination of female Aedes aegypti mosquitoes from the rearing process showed positive results for Dengue virus. Abstrak: Demam Berdarah Dengue (DBD) merupakan masalah kesehatan di Kelurahan Kembangan Utara, Kecamatan Kembangan. Terdapat angka kejadian DBD September 2022 136 kasus dengan jumlah penduduk 68.841 dengan IR sebesar 197,6. Melihat tingginya kasus tersebut, maka perlunya kegiatan koordinasi survei kepadatan vektor dan pemeriksaan virus Dengue pada nyamuk Aedes aegypti. Tujuan penelitian: Terlaksananya koordinasi kegiatan untuk survei kepadatan vektor dan pemeriksaan virus Dengue pada nyamuk Aedes aegypti. Metode penelitian observasi yang dilakukan dengan mengamati keberadaan jentik Aedes aegypti ditinjau dari tempat perindukan. Observasi dilakukan dengan lembar observasi. Analisis Statistik untuk mendeskripsikan gambaran tempat perindukan, kepadatan, dan jenis-jenis tempat perindukan yang dominan disukai jentik nyamuk Aedes aegypti. Hasil survei jentik nyamuk di 100 rumah menunjukkan 31 rumah positif jentik (ABJ:70%), artinya wilayah Kelurahan Kembangan Utara, Kecamatan Kembangan, Jakarta Barat termasuk risiko tinggi terjadinya penularan DBD. Penangkapan nyamuk pada 100 rumah menunjukkan 80 rumah ditemukan nyamuk 142 ekor yang terdiri dari genus Culex yaitu 123 ekor, nyamuk Aedes aegypti betina yaitu 8 ekor dan nyamuk Aedes aegypti jantan yaitu 11 ekor. Pemeriksaan virus Dengue nyamuk Aedes aegypti betina dari proses rearing menunjukkan hasil positif virus Dengue. Kesimpulan pemeriksaan virus Dengue nyamuk Aedes aegypti betina dari proses rearing menunjukkan hasil positif virus Dengue.